Model Kepuasan Kerja: Eksplorasi Peran Faktor Psikososial melalui Kinerja Pegawai pada Pengadilan Negeri Tegal, Slawi, dan Brebes - Dwi Mei Diana Sintiyawati; Rahmatika, Dien Noviany; Raharjo, Teguh Budi (Universitas Muhammadiyah Pontianak, 2026)
A fundamental debate in human resource management questions the causal direction between job satisfaction and employee performance. Drawing on Expectancy Theory and Achievement Motivation Theory, this study positions performance as a mediator between psychosocial work conditions and job satisfaction. Using a quantitative census of 124 civil servants at the Tegal, Slawi, and Brebes District Courts (109 usable responses), data were analyzed with PLS-SEM. Work-life balance and the work environment positively affect performance, while work overload has a negative effect. Only the work environment directly affects satisfaction; employee performance fully mediates the effects of work-life balance and work overload.